2019
DOI: 10.1142/s2424835519500553
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Early Post-Operative Radiographs Following Distal Radius Fracture Fixation with a Volar Locking Plate: Time for Change?

Abstract: Background: The role of early radiographic imaging in the management of distal radius fractures (DRFs) is unclear. The aim of this study was to assess whether early post-operative radiographs for DRFs influences the ongoing management of this patient group. We hypothesize that routine early radiographs do not influence the management of DRFs. Methods: This was a retrospective review of patients undergoing open reduction and internal fixation using a volar locking plate between 2012 and 2017 at our institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Most studies were based on case series ( n = 33) 22,31,33,34,36,38,41,43‐50,56,57,60‐64,66,68‐72,74,75,77,85,89,90 followed by systematic reviews with or without meta‐analysis ( n = 12), 23‐25,28,29,39,53,59,67,78,83,86,88,91 prospective cohorts ( n = 9), 30,32,35,37,42,51,54,79,87 RCTs ( n = 9) 27,55,65,73,80‐82,84 and retrospective cohorts ( n = 2; Supplemental Digital File ) 52,58 …”
Section: Resultsmentioning
confidence: 99%
“…Most studies were based on case series ( n = 33) 22,31,33,34,36,38,41,43‐50,56,57,60‐64,66,68‐72,74,75,77,85,89,90 followed by systematic reviews with or without meta‐analysis ( n = 12), 23‐25,28,29,39,53,59,67,78,83,86,88,91 prospective cohorts ( n = 9), 30,32,35,37,42,51,54,79,87 RCTs ( n = 9) 27,55,65,73,80‐82,84 and retrospective cohorts ( n = 2; Supplemental Digital File ) 52,58 …”
Section: Resultsmentioning
confidence: 99%
“…For fracture reduction and fixation, the value of early postoperative radiographs in the treatment of distal radius fracture fixation has been questioned, and some studies have demonstrated that these images do not change postoperative management. 20 , 21 , 22 Sharma et al 21 found that among 172 patients with early postoperative radiographs following distal radius fracture fixation, only 7 patients had alterations in their postoperative management with only 1 patient requiring immediate surgical revision as indicated by imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were based on case series (n=33) 22,31,33,34,36,38,41,[43][44][45][46][47][48][49][50]56,57,[60][61][62][63][64]66,[68][69][70][71][72]74,75,7785,89,90 followed by systematic reviews with or without meta-analysis (n=12) [23][24][25]28,29,39,53,59,67,78,83,86,88,91 , prospective cohorts (n=9) 30,32,35,37,42,…”
Section: Study Characteristics According To Categories Of Low Value Practicesmentioning
confidence: 99%
“…78,83 , two RCTs 82,84 , three cohort studies (one prospective) 42,52,58 and 32 case series31,33,34,36,41,[43][44][45][46][47][48][49][50]56,57,[60][61][62][63][64]66,[68][69][70][71][72][74][75][76][77]85,89,90 evaluating routine post-treatment imaging and follow-up consultations.…”
mentioning
confidence: 99%